Lairage periods on temperament score and meat quality of beef cattle - Moura, Sandra Vieira de; Silveira, Isabella Dias Barbosa; Ferreira, Otoniel Geter Lauz; Mendonça, Fábio Souza; Moreira, Sheilla Madruga; Restle, João; Garcia, Javier Alexandre Bethancourt; Vaz, Ricardo Zambarda (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the influence of lairage periods on the temperament, physiological indicators of stress, and meat quality of beef cattle. Thirty-two castrated Aberdeen Angus x Nellore crossbred steers were distributed into four lairage periods: 12, 18, 24, and 48 hours. The following variables were evaluated: serum levels of the physiological indicators of stress glucose and cortisol (upon arrival at the slaughterhouse, after the lairage period, and at bleeding), animal temperament (movement, resistance to approach, and aggressiveness), and meat quality (final pH, water-holding capacity, color parameters, and tenderness). With a longer lairage period, the temperament score was higher, indicating that the animals were more agitated and resistant to human approach. Serum cortisol and glucose levels correlate positively with animal temperament and negatively with meat quality. At bleeding, an increase was observed in glucose and cortisol levels, respectively, for lairage periods longer than 24 hours and of 12 hours. The lairage of 48 hours reduces meat tenderness and water-holding capacity.